Sexualidade e gênero na educação infantil: o que as teses e dissertações dos programas de pós-graduação em Educação contam e silenciam - Carvalho, Rita de Cássia (2021)
This doctorate research is composed by several sub-projects under development in the project Public Policy and Children’s Education in Goiás: history, concepts, projects and practices, of a group that studies childhood and its education, linked to the research line Training, Teachers’ Professionalization and Educational Practices of the Postgraduate Program in Education of the Faculty of Education of Federal University of Goiás. We believe that discussing and working with sexuality and gender with children in Early Childhood Education is an important and necessary task, since sexual and gender identities are under development in this age group, since birth, based on interaction and mediation processes with more experienced subjects and with cultural elements, which help these children appropriate meaning about the world they live in and, in particular, about sexuality and gender, through games, observations, questions, transgressions and resistance. Therefore, inspired by the state of knowledge methodology and content analysis, we propose to investigate what the theses and dissertations of the Graduate Programs in Education, indexed in the database of the Coordination for the Improvement of Higher Education Personnel ( Capes) and the Brazilian Digital Library of Theses and Dissertations (BDTD), disclose and withhold about sexuality and gender in / for / with Early Childhood Education. To this end, we used Boolean operators which assisted in surveying research on our theme, enabling cataloging as to: the type of research, year of defense, gender of researchers / regions, regions of Brazil, Higher Education Institutions and research groups. In order to verify the production of articles on the theme, we carried out a bibliographic survey in a Children's Education Work Group dealing with children 0 to 6 years of age (GT07) and a Gender, Sexuality and Education (GT23) Work Group from the National Association of Graduation and Research in Education (Anped), in SciELO and in the CAPES (a Brazilian federal government agency under the Ministry of Education, responsible for quality assurance in undergraduate and postgraduate institutions in Brazil) periodical portal. For analysis of the chosen researches, readings of: title, summary, keywords, summary and introduction were carried out, checking if they met the criteria established by us and, we observed that of the 91 elected studies, 43 met our purposes. From reading and analyzing the chosen works and, based on historical dialectical materialism, we dialogued with the objects, observing their propositions, realities and contradictions, and extracted from them the following categories for analysis: education / disciplinarization of children's bodies, the institution's daily education routine and its pedagogical practices, the use of toys and games in sexuality and gender education, as well as in the construction of children's identities and the transgression / resistance of children in / of early childhood education in the face of the norms and rules imposed on them. The analysis of the categories showed us how sexuality and gender are explored in Early Childhood Education, influencing the construction of sexual and gender identities, as well as what has been suppressed by educational institutions in terms of sexuality and gender - the transgender traits exhibited by some children between zero and six years of age.